ANALYTICAL STUDY OF NATURAL DRAUGHT COOLING TOWER ON VERTICAL PILES USING FINITE ELEMENT METHOD (Malaysian Journal of Civil Engineering, 2018)
The study aimed to analyse the behavior of natural draught cooling tower (NDCT) resting on a vertical pile foundation specifically focusing on prevailing soil conditions in the coastal areas. 27 different cases of shell thickness variation models are studied. The study adopted FEM analysis of NDCT and its foundation as a composite model which also facilitate to study the impact of providing a vertical pile foundation on the behavior of NDCT super structure. Results demonstrated that the reactions on all the piles are within the allowable pile capacities in all cases 1 to 27. In addition, our arc over which lift occurs in the foundation was 0Âº.The pile support reactions indicate that the horizontal loads on all the piles are varying based on the loads from the superstructure and when the NDCT super structure and its foundation were analysed with composite model.Maximum displacement of the shell and pile forces are reducing by increasing the top level of bottom ring beam.Further, our paper did show the deflection profile and pile reaction variation profile closer to realistic/actual behavior of NDCT than a conventional model.Therefore, the methodology adopted in this paper to study the behavior of 3D modeling of NDCT and its foundation could able to predict the dynamic responses of wind structure. From the results of the study it was established that in coastal areas NDCT can be supported on simple vertical piles instead of conventional raker piles. Further the study also identified optimum shell thickness profiles to be adopted to obtain the optimum foundation and the superstable structure for NDCT resting on vertical pile foundation.